PENGARUH PENGEMBANGAN KOMPETENSI TERHADAP KINERJA DOSEN DENGAN VARIABEL MODERATOR KOMITMEN TENTANG MUTU - -, Lamidi - (Universitas Slamet Riyadi, 2007)
ABSTRACT This research is aimed to find the influence of commitment quality as variable in moderate of the correlation between competencies development with performance of lectures. Population in this research are all lectures in area of economics faculty Slamet Riyadi University Surakarta with sampel are 31 respondent. The instrument used questionaire with Likert scale technique. Data analysis using multiple regression analysis. Result of hypothesis test indicate that that of commitment quality to influence towards level of relationship between competencies development with performance of lectures. Keywords: commitment quality, competencies development, performance of lectures.